2016
DOI: 10.3839/jabc.2016.040
|View full text |Cite|
|
Sign up to set email alerts
|

Eye and skin irritation tests using deep sea water-extracted minerals

Abstract: Deep sea water (DSW) contains many inorganic materials and minerals, which are extracted for use in diverse fields. However, before application, safety tests should be performed. In the present study, two DSW-extracted minerals were analyzed: calcium (Ca) and magnesium (Mg). Eye and skin irritation tests of DSW-extracted Ca and Mg were performed according to the guidelines of the Ministry of Food and Drug Safety of Korea. These two types of mineral extracts caused no symptoms of eye and skin irritation when co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Additionally, hypomagnesemia due to low serum magnesium concentration is also associated with insulin resistance and diabetes mellitus (Sales and Pedrosa Lde 2006). Indeed, sufficient magnesium intake is known to reduce the development of diabetes mellitus (Joo et al 2016). Recently, some research groups have found that deep seawater elicits positive effects on diabetes mellitus (Ha et al 2013) and inhibits adipogenesis (Ha et al 2014).…”
Section: +mentioning
confidence: 99%
“…Additionally, hypomagnesemia due to low serum magnesium concentration is also associated with insulin resistance and diabetes mellitus (Sales and Pedrosa Lde 2006). Indeed, sufficient magnesium intake is known to reduce the development of diabetes mellitus (Joo et al 2016). Recently, some research groups have found that deep seawater elicits positive effects on diabetes mellitus (Ha et al 2013) and inhibits adipogenesis (Ha et al 2014).…”
Section: +mentioning
confidence: 99%